If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2x = -1x + 9 Reorder the terms: -2x = 9 + -1x Solving -2x = 9 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. -2x + x = 9 + -1x + x Combine like terms: -2x + x = -1x -1x = 9 + -1x + x Combine like terms: -1x + x = 0 -1x = 9 + 0 -1x = 9 Divide each side by '-1'. x = -9 Simplifying x = -9
| y^2+6y-2=0 | | 6m^2=66m-168 | | 10x-35=90x+120 | | x^2+5x-6x=0 | | Y=12x^2-26-16 | | 6x+13=311 | | (2n-7)(5n+20)=0 | | 9x+14=50 | | 0.25(m-4)+0.25m=3 | | -9x-154=2x+77 | | x-6x-2=3 | | -2(x+3)=4x-3-2 | | 24x^2=9xy | | -35-8x=8-8(6+x) | | 4p-3=p+8 | | 7x+0.125=x-0.75 | | 3x+(50x-5)=30 | | V-17=2 | | (5y-1)(2y+4)=0 | | -12-6x=-5x+12 | | 16x-12y=53 | | A^2=7a-6 | | 2(x+4)+x=12+x | | -65-11x=-4x+40 | | Ln(4x-1)=6 | | 0.75m-5-0.50m=1 | | 15x-25(5)=-115 | | -21+5x=51+9x | | 3.5x=2800 | | 10x-15y=53 | | 4x-12=46 | | 6=20-2 |